ANALYSIS OF SECURITY VULNERABILITY LEADING E-COMMERCE PLATFORMS USING OWASP (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
The rapid growth of the e-commerce sector in Indonesia is directly proportional to the increasing risk of cyberattacks targeting transaction data and users' sensitive information. Large-scale e-commerce platforms with millions of active users become highly vulnerable targets if their web-based applications contain security flaws. This study aims to identify, analyze, and evaluate the risk levels of security vulnerabilities on a leading e-commerce platform in Indonesia using the Open Web Application Security Project (OWASP) framework. This research applies the Vulnerability Assessment and Penetration Testing (VAPT) method, guided by the Open Web Application Security Project (OWASP) standards. The results showed the presence of 30 alerts, including potential security vulnerabilities in the web system, whose risk levels were then classified using the Common Vulnerability Scoring System (CVSS). The e-commerce platform was declared sufficiently secure against direct penetration attacks on the database but remains vulnerable to end-user access manipulation. These findings provide an objective overview of security in large-scale digital retail systems. The implications of this research are expected to serve as technical recommendations for platform developers in mitigating and patching security flaws, as well as a theoretical reference in developing cybersecurity governance strategies within the electronic commerce ecosystem in Indonesia.